Peran Mediasi Komitmen Organisasi pada Pengaruh Beban Kerja terhadap Kinerja Karyawan - Indra Setiawan (Jesya (Jurnal Ekonomi dan Ekonomi Syariah), 2021)
The purpose of this study is to determine whether there is an effect of workload on employee performance mediated by organizational commitment. The object of research at PT KY Indonesia, Cikarang. The research was conducted using quantitative methods with SEM Smart PLS software as an analysis tool. The number of samples obtained by random sampling using the Slovin formula totaled 57 respondents. Data collection is done by using google forms in filling out online surveys. The data analysis method used is the R-square test, Bootstrapping, Path Coefficient, and Specific indirect effects. The results of this study indicate that workload affects employee performance, the workload has a positive and significant effect on organizational commitment, organizational commitment has a positive and significant impact on employee performance, organizational commitment can have a positive influence in mediating the relationship between workload and employee performance in PT KY Indonesia.